A review on the recent developments in thermal management systems for hybrid-electric aircraft. (5th June 2023) - Coutinho, Maria; Bento, David; Souza, Alain; Cruz, Rodrigo; Afonso, Frederico; Lau, Fernando; Suleman, Afzal; Barbosa, Felipe R.; Gandolfi, Ricardo; Affonso, Walter; Odaguil, Felipe I.K.; Westin, Michelle F.; et al.
Abstract: The electrification of aircraft propulsive systems has been identified as one of the potential solutions towards a lower carbon footprint in the aviation industry. However, there are still several environmental and technological challenges associated with the propulsion electrification. One of these challenges is the development of adequate thermal management systems that are lightweight and can cope with the higher heat loads estimated for all-electric and hybrid-electric aircraft when compared with conventional architectures. Addressing this latter issue is therefore an operational requirement for more electric aircraft. There are several solutions proposed in the literature to tackle this challenge at different levels of development. The main focus of the current paper is to provide a critical review on the existing solutions. From this review, liquid cooling loops integrated with ram air heat exchangers seem to be the most viable ones with nowadays technology. However, in the future the introduction of nanofluids with higher thermal conductivities and skin heat exchangers can be an interesting solution to improve performance. Highlights: Heat transfer technologies are identified and discussed considering their potential. A critical overview on Thermal Management System (TMS) architectures is provided. Promising solutions and challenges for hybrid-electric aircraft are pointed out. The focus is on recent developments for commercial hybrid-electric aircraft.